2008
DOI: 10.1590/s1677-55382008000100003
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study comparing six - and twelve-core prostate biopsy in detection of prostate cancer

Abstract: Objective: We compared the safety and efficacy of the 12-core biopsy with those of the conventional systematic 6-core biopsy with PSA levels between 4.1 and 20.0 ng/mL. Materials and Methods: This study included 428 patients who underwent a 6-core biopsy and 128 patients who underwent a 12-core biopsy. Biopsies were performed transrectally under ultrasound guidance. The 12-core biopsy scheme involved obtaining 6 far lateral cores. Results: For patients with PSA level between 4.1 and 10.1 ng/mL, 47 of the 265 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Out of 36 patients who had the procedure under local anaesthetic none of the patients had post procedure complications like rectal bleeding, need for anaesthesia or prolongation of hospitalization. Similar studies by Tobiume et al 21 none of the patients showed rectal bleeding or need for anaesthesia, only few patients had minor complications.…”
Section: Correlation Of Complications Post Trus Biopsysupporting
confidence: 83%
“…Out of 36 patients who had the procedure under local anaesthetic none of the patients had post procedure complications like rectal bleeding, need for anaesthesia or prolongation of hospitalization. Similar studies by Tobiume et al 21 none of the patients showed rectal bleeding or need for anaesthesia, only few patients had minor complications.…”
Section: Correlation Of Complications Post Trus Biopsysupporting
confidence: 83%
“…Third, the bmiPCPTRC was built upon the original PCPTRC which relied on 6-core biopsies, and may lead to lower rates of PCa or HGPCa detection compared with the current standard of minimum 6-core biopsies. 29-30 Fourth, 614 men were excluded from the final analysis due to missing PSA, DRE, or BMI, and the PCa rate among these excluded men was significantly lower than those included in the analysis. This contributes to the higher PCa risk in the current cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have been conducted with different modifications in order to make it less invasive and to increase the sensitivity/specificity. 2,4,6 Recently, it has been asserted that the utilization of TRUS-pBx combined with targeted multiparametric magnetic resonance imaging (MRI) can improve prostate CDRs, especially the clinically significant ones, which is getting more and more popular. 8 It is believed that the zonal anatomy of the prostate and the number of biopsy cores are the key factors in the detection of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%